Finite element analysis of flexural performance of reinforced truss hollow composite concrete slabs - Xudong Chen; Yunlin Liu; Qinyong Ma; Peng Zhou; Xuan Liu; Jiajian Lin (Scientific Reports)
Abstract Combining the advantages of cast-in-place hollow slabs and prefabricated reinforced truss composite concrete slabs, a novel hollow composite slab is proposed, characterized by the inclusion of hollow thin-walled boxes without reinforcement at the edges, referred to as the hollow composite slab. To further investigate the flexural performance and critical design parameters of the hollow composite slab, numerical simulations were conducted using the finite element software ABAQUS. Based on the actual specimen fabrication and test results, the rationality of the finite element modeling was validated. Using the finite element model, a parametric analysis of key parameters for the specimens was conducted. The results showed that the finite element model could effectively simulate the crack distribution, flexural performance, and deformation characteristics of hollow composite slabs. The influence of concrete strength and the longitudinal dimension of hollow thin-walled boxes on the flexural performance of hollow composite slabs was minimal, with ultimate bearing capacities changing by only 4.63% and 0.91%, respectively. In contrast, changes in slab thickness and span had a significant impact on the flexural performance, with ultimate bearing capacities changing by 20.46% and 42.09%, respectively. The bearing capacity of hollow composite slabs increased significantly with increasing slab thickness but decreased markedly with increasing span.